1992
DOI: 10.1002/tea.3660290609
|View full text |Cite
|
Sign up to set email alerts
|

Grade‐12 students' misconceptions relating to fundamental characteristics of atoms and molecules

Abstract: An understanding of the concepts of atom and molecule is fundamental to the learning of chemistry. Any misconceptions and alternative conceptions that students harbor about these concepts will impede further learning. This article identifies misconceptions related to the fundamental characteristics of atoms and molecules which Grade‐12 students hold. Data were obtained by administration of semistructured interviews to a stratified, random sample of 30 students of differing abilities and backgrounds in science.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
246
0
74

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(329 citation statements)
references
References 27 publications
9
246
0
74
Order By: Relevance
“…Although symbolic and microscopic representations are frequently used in chemistry textbooks, applying ideas of particles and constructing microscopic representations to make explanations of observations are very difficult for many secondary school students (Brosnan & Reynolds, 2001;Griffiths & Preston, 1992;Renstroem, Andersson, & Marton, 1990). They usually represent chemical concepts or phenomena at the macroscopic level rather than microscopic or symbolic levels.…”
Section: Difficulties In Comprehending and Interpreting Representationsmentioning
confidence: 99%
“…Although symbolic and microscopic representations are frequently used in chemistry textbooks, applying ideas of particles and constructing microscopic representations to make explanations of observations are very difficult for many secondary school students (Brosnan & Reynolds, 2001;Griffiths & Preston, 1992;Renstroem, Andersson, & Marton, 1990). They usually represent chemical concepts or phenomena at the macroscopic level rather than microscopic or symbolic levels.…”
Section: Difficulties In Comprehending and Interpreting Representationsmentioning
confidence: 99%
“…In another study, molecular spacing in gases has been found underestimated, while the particle motion has been ignored by the majority of the students (Pereira & Pestana, 1991). Misconceptions have been also reported in relation to particle size of a substance that is thought to vary in different states (Dow et al, 1978;Griffiths & Preston, 1989;Pereira & Pestana, 1991).…”
Section: Introductionmentioning
confidence: 97%
“…Talk of 'solids', 'liquids' and 'gases' may lead pupils to think that these are three separate kinds of Author#3, 1996) and hence there must be three types of particle which carry the respective macroscopic properties, a common misconception (e.g. Andersson, 1990;Ben-Zvi, Eylon, & Silberstein,1986;Gabel & Sumuel 1987;Griffiths & Preston, 1992;Kokkotas, Vlachos & Koulaidis, 1998;Pereira & Pestana, 1991). Changes of state in some instances are then seen as perplexing anomalies.…”
Section: Introductionmentioning
confidence: 99%